Identification of Affixation in Selulung Dialect - Karsanata, I Putu Anom (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
This research aimed at investigating the’ affixation used in Selulung Dialect. The current study was qualitative study and employing Interactive Model Analysis proposed by Miles & Huberman (1994) as the model of data analysis. Through the researcher itself as the main instrument and supported by interview guide, note taking, observation list, word sheet, and recorder, the data were collected. By involving three informants, the data revealed 130 words with affixation and three kinds of affixation process. Those are Prefix N-, a-, ma-, pa-, ka-, Suffix -a, -e, -in, -ang, -an, -ne, -ane, Combination of Affix (Confix) N-in, N-ang, ma-an, and ma-ang. The most frequent affix used by the villagers in Selulung is prefix N- with 38 words (29.23%) and it has four allomorphs, namely |n-|, |m-|, |ng-|, |ny-|.